Continuous De-emulsification of Crude Oil Using Packed Column Under Various Conditions - R. Rassoul, G. A. (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
This research dealt with desalting of East Baghdad crude oil using pellets of either anionic, PVC, quartz, PE, PP or nonionic at different temperature ranging from 30 to 80 °C, pH from 6 to 8, time from 2 to 20 minutes, volume percent washing water from 5 to 25% and fluid velocity from 0.5 to 0.8 m/s under voltage from 2 to 6 kV and / or using additives such as alkyl benzene sulphonate or sodium stearate. The optimum conditions and materials were reported to remove most of water from East Baghdad wet crude oil.